Diversidad de anfibios y reptiles en hábitats altoandinos y paramunos de la cuenca del río Fúquene, Cundinamarca, Colombia (2014)
Nowadays, the high-Andean and paramo ecosystems from Colombia are threatened as a result of habitat degradation, which has caused that some groups, like amphibians and reptiles, are under some threat category. It was done the first analysis of species richness in the Fúquene river basin, in the department of Cundinamarca, in different habitats in transects between 2600 and 3100 m a.s.l. It was performed a systematic sampling, during the day and at night, looking for amphibians and reptiles in three characteristic habitats: paramo, riparian forest and high-Andean forest. There were found two species of frogs and five of reptiles in the study area, It was reached a sample representation of 100% in each habitat. Although there are not previous records of amphibian and reptiles in the study area, the results were compared with a check list for near localities in similar elevations. The habitat degradation and contamination, caused by agricultural activity and livestock, may be related with the low diversity of amphibians and reptiles in the region.